Anthracene aquacracking using NiMo/SiO2 catalysts in supercritical water conditions. (15th October 2016) - Reina, T.R.; Yeletsky, P.; Bermúdez, J.M.; Arcelus-Arrillaga, P.; Yakovlev, V.A.; Millan, M.
Graphical abstract: Highlights: Effective NiMo/SiO2 catalysts for anthracene upgrading in supercritical water conditions. Influence of the Ni/Mo ratio in the activity and selectivity. Anthracene oxidation preferentially proceeds through the middle ring. Valuable gaseous products: high hydrogen yields. Abstract: A series of effective NiMo/SiO2 catalysts for heavy oil upgrading in supercritical water have been developed. Experimental results with anthracene as model compound resembling structures present in heavy oils showed that the catalytic activity as well as the liquid and gas product distributions are governed by catalyst composition. In particular by adjusting the Ni/Mo ratio different physicochemical properties (crystalline phase composition, particle size and catalysts reducibility) are obtained, which have influence on catalytic behavior. A variety of liquid products together with a valuable gas (rich in H2 ) are produced in this process, which takes place with remarkably low coke deposition on the catalysts. Overall, the results derived from this work confirm the viability of upgrading polyaromatic structures in supercritical water using Ni-Mo catalysts and provides an insight on the main parameters to control in catalyst design.